Hybrid multiplier/CORDIC unit for online handwriting recognition - REILLY, RICHARD (IEEE, 1999)
Traditionally online handwriting recognition (OHR) implementations use general-purpose processor architectures. The pre-processing step of OHR comprises regular array-based tasks such as normalisation, feature extraction and segmentation. Standard processor architectures cannot however efficiently support the varied arithmetic operations required by pre-processing. These tasks would seem ideally suited for custom hardware acceleration. CORDIC offers all the required elementary functions for pre-processing but is inefficient for linear mode operations (multiplication/division) due to its serial nature. A hybrid multiplier/CORDIC architecture is proposed in which a fast iterative multiplier/MAC shares hardware with a serial CORDIC unit. This multiplier retires 6b/cycle with minor additional hardware requirements. This hybrid offers improved general performance for signal-processing applications and is targeted at the pre-processing task of OHR. Performance results are included
PUBLISHED
Keywords: Administrative Staff Authors